2012
DOI: 10.6028/nist.tn.1747
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Smoldering Performance of Polyurethane Foam

Abstract: The objective of this study was to evaluate whether polyurethane foam (PUF) could be produced as a Standard Reference Material for ultimate use in a standard test intended to ensure the smoldering performance of commercially available upholstered furniture. For this purpose, PUF was produced by a commercial manufacturer and its smoldering propensity was evaluated. The experimental design was organized into four parts or "Iterations". In Iteration 1, the results showed that smoldering intensity was dominated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Correlation between total heat transferred and area density of the barrier fabrics (BFs). Uncertainties are reported as Type A uncertainties with experimental standard deviations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation between total heat transferred and area density of the barrier fabrics (BFs). Uncertainties are reported as Type A uncertainties with experimental standard deviations.…”
Section: Resultsmentioning
confidence: 99%
“…A lower amount of heat was transferred (30 ± 8 MJ/m 2 ) through BF-18, compared to BF-15, which was 75 ± 7 MJ/m 2 . The higher heat transfer though BF-15 could be due to its higher porosity and hence higher Uncertainties are reported as Type A uncertainties [21,22] with experimental standard deviations. permeability of the woven structure.…”
Section: Heat Transfer Properties Of Barrier Fabricsmentioning
confidence: 99%
“…32 The FPUF foam used in this study was a well characterized flexible polyurethane foam 32 especially developed for evaluating upholstery materials and their tendency to support smoldering or limit flaming combustion. 33 The masses of the vertical (203 × 203 × 76) mm³ and horizontal (127 × 203 × 76) mm³ FPUF sections were recorded and used later to calculate the fraction that smoldered. The FPUF was covered with the BF, and, in turn, by the cover fabric (Indigo Buckaroo Denim purchased from Jo Ann Fabrics was used in this study), and the entire ensemble was placed in the wooden frame.…”
Section: Experimental Materials and Test Methodsmentioning
confidence: 99%
“…Both for obtaining reference data and for subsequent screening of alternate ignition sources, there needed to be a sufficient amount of uniformly ignition-susceptible material for a large number of tests. Variations in the properties of FPUF can affect its smoldering performance [35], so the specimens were cut from a block of foam whose ignition uniformity had been previously examined. It was also necessary that an SRM 1196 cigarette ignite the fabric/foam substrate some, but not all, of the time in a series of replicate tests.…”
Section: Reactive Substratesmentioning
confidence: 99%
“…Fortunately, recent research has identified properties of FPU foams that affect the extent of smoldering [35] and, probably, the foam's contribution to smoldering ignition. Thus, large, relatively uniform batches of FPUF can be ordered.…”
Section: To What Extent Does a Chemical Interaction Between The Ignitmentioning
confidence: 99%